Association between exposure to greenspace and ECG abnormalities in China: a nationwide longitudinal study - Zhaoyang Pan; Man Cao; Xueyan Han; Jian Guo; Dengmin Huang; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (BMC, 2024)
Abstract Background Greenspace is an important modifiable environmental factor that is associated with health and well-being. Although previous research has shown that exposure to greenspace is beneficial for cardiovascular diseases, studies have rarely focused on early subclinical health outcomes such as electrocardiogram (ECG) abnormality. Methods We developed a longitudinal study using data from the China National Stroke Screening Survey (2013-2019). Monthly exposure to greenspace was assessed by the Normalized Difference Vegetation Index (NDVI) values. ECG abnormality was diagnosed by physicians based on the results of the 12-lead electrocardiogram. We used fixed-effects logistic regression with participant-specific intercepts to estimate the association between exposure to greenspace and ECG abnormalities. Results A total of 132,108 visits from 61,029 participants with ≥ 2 ECG measurements were included. At baseline, the lag-1 month average NDVI value was 0.29 (SD = 0.15). In the fully adjusted model, per 0.1-unit increment in lag-1 month average NDVI value was associated with a 3.0% (95% CI -1.6 ∼ 7.4%) decreased risk of ECG abnormality. In urban areas, the decreased risk associated with per 0.1-unit increment in NDVI was 14.81% (95% CI 9.38 ∼ 19.92%). Conclusion Our study found that higher exposure to greenspace was associated with a decreased risk of ECG abnormality, especially in urban areas. Our findings suggested that monthly exposure to greenspace might be beneficial to cardiovascular health, and greenspace provision and maintenance could be considered an important public health intervention in urban planning.